Mitigation of thermal distortion in wire arc additively manufactured Ti6Al4V part using active interpass cooling - Wu, Bintao; Pan, Zengxi; Chen, Guangyu; Ding, Donghong; Yuan, Lei; Cuiuri, Dominic; Li, Huijun (Maney Publishing, 2019)
In this study, active interpass cooling using compressed CO2 was innovatively employed in the wire arc additively manufactured Ti6Al4V process with the aim of mitigating part distortion. A comparative analysis between simulation and experimental results was performed to explore the effects of active interpass cooling on the thermal behaviours, geometric features and distortion levels of deposit. The results show that active interpass cooling with CO2 gas is an effective means of reducing Wire arc additive manufacturing (WAAM)-part distortion by increasing heat dissipation and reducing heat accumulation within the deposition. It can contribute to a maximum reduction of 81% in longitudinal distortion and 69% in transverse distortion for the wall structures produced in this study. Compared to the cooling gas flow rate, cooling time alternation is more effective in mitigating WAAM-part distortion due to more effective heat dissipation per unit time. The findings reveal that using active interpass cooling in WAAM can offer significant cost and build-time savings, as well as providing conditions for the improvement of WAAM-part quality.
Keywords: Wire arc additive manufacturing; Ti6Al4V; active interpass cooling; distortion